Pinguicula filifolia subsp. alba (Lentibulariaceae), a new subspecies with an extremely restricted distribution in Pinar del Río, Cuba - Domínguez, Yoannis; Valdés, Cristina M Panfet; De Miranda, Vitor F.O. [UNESP] (Magnolia Press, 2014)
The carnivorous plant Pinguicula filifolia occurs in western Cuba and shows a restricted distribution due to habitat specificity associated with poor wet soils. Its populations are distributed mainly in south Pinar del Río (Cuba) and in Isla de la Juventud. Plants from one isolated location in NW Pinar del Río shows morphological differences with respect to the rest of the known populations observed in nature. Subsequent detailed morphological analysis of specimens led to the description of Pinguicula filifolia subsp. alba as a new subspecies. It differs from the typical subspecies in several reproductive traits involving flower, fruit and seed characters and is so far known only from the type locality. © 2014 Magnolia Press.
Keywords: Morphology; Taxonomy; Western Cuba